What factors will impact on the adoption of digital technology to access general practitioners in Australia? - Jiwa, Moyez; Asteljoki, Sara; Pagey, Georgina (Radcliffe Medical Press Ltd., 2013)
The geography of large and relatively underpopulated countries like Australia makes it attractive to use increasingly cheap information technology to improve access to general practitioners. People are already using the internet to access many other services. However, there are some moderating influences on the use of video-consultations in general practice. These include technical limitations, patient confidentiality concerns, regulatory issues as well as the willingness of general practitioners to consult patients other than face-to-face. Theories predict that a relatively small cadre of innovative doctors are those most likely to try video-consultations for routine consultations. However, much will depend on research that demonstrates that video-consultations are unlikely to harm patients or increase the risk of litigation; on the scope to incorporate diagnostic equipment on home computers; on the financial incentives offered to doctors and on the public proclamations of opinion leaders on the question of video-consultations.